2022
DOI: 10.54410/denlojad.1211835
|View full text |Cite
|
Sign up to set email alerts
|

Human Resources Manager Selection Based on Fuzzy and Intuitionistic Fuzzy Numbers for Logistics Companies

Abstract: Qualified managers are needed for the systematic functioning of logistics management applications. In logistics companies, the human resources manager takes part in determining the amount of personnel needed, supplying personnel, and creating personnel task forms. For successful human resources management, a qualified human resources manager should be selected. In the literature, it is seen that the manager selection problem is handled with multi criteria decision making (MCDM) methods. The aim of this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…One of the most significant problems in personnel selection is the presence of bias and discrimination [6]. Recruiters may be influenced by biases based on age, gender, race, ethnicity, or other personal characteristics, which can lead to unfair and inequitable hiring decisions [7].…”
Section: The Problem Of Personnel Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most significant problems in personnel selection is the presence of bias and discrimination [6]. Recruiters may be influenced by biases based on age, gender, race, ethnicity, or other personal characteristics, which can lead to unfair and inequitable hiring decisions [7].…”
Section: The Problem Of Personnel Selectionmentioning
confidence: 99%
“…Personnel selection systems are decision support systems that generate a result showing a ranking for each potential employee, so that management decision makers can see the capability of each potential employee based on the ranking [5,6,14]. Generally speaking, it can be stated that personnel selection systems are among the most complex organizational and intellectual processes and of necessary precision [15,16] There are organizations that already apply personnel selection systems in order to optimize this activity [9]; something that as a result of the pandemic contingency has forced other organizations to use and implement this type of systems [17], in this way the use of personnel selection systems is beginning to become widespread around the world.…”
Section: Personnel Selection Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This section foregrounds the intricacies of personnel selection across various logistical roles, drawing upon diverse MCDM methodologies. In a study conducted within the Turkish context (Kara et al, 2022), a set of ten criteria were distilled for the selection of HRM managers. Here, a hybrid decision-making approach was adopted, entailing the application of the Intuitionistic Fuzzy Weighted Averaging (IFWA) technique for the determination of criteria weights, succeeded by the implementation of the Fuzzy Multi-Attribute Ideal-Real Comparative Analysis (F-MAIRCA) for candidate ranking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The criteria for evaluation were established through an examination of pertinent literature and an analysis of the competencies delineated in job descriptions for the role. Some criteria emerged independently, while others were refined based on the aforementioned literature (Cvetić et al, 2019;Jakeš, 2016;Kara et al, 2022;Karabasevic et al, 2015) Seven criteria were identified for the selection process:…”
Section: Case Study Of a Transport Manager Selection Processmentioning
confidence: 99%